2022
DOI: 10.3390/jmse10091169
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Performance of a Catamaran in Shallow Waters

Abstract: The effects of limited water depth on the hydrodynamic performance of a catamaran with the full-scale dimensions and geometry of a WAM-V 16 unmanned surface vehicle operating in shallow waters are investigated using an incompressible URANS-VOF solver in OpenFOAM®. Simulations of the flow associated with the passage of the catamaran in shallow waters have been conducted for a range of vehicle speed and several shallow to intermediate water depths under free trim and sinkage conditions. The effects of water dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…When operating in shallow water, the shallow water effect on the total resistance, trim, and sinkage of the catamaran should be taken into account. Ulgen and Dhanak [13] showed that the total resistance coefficient of the catamaran increases by over 40% at transcritical Froude numbers, which are close to the critical value of the Froude number based on water depth.…”
Section: Introductionmentioning
confidence: 54%
“…When operating in shallow water, the shallow water effect on the total resistance, trim, and sinkage of the catamaran should be taken into account. Ulgen and Dhanak [13] showed that the total resistance coefficient of the catamaran increases by over 40% at transcritical Froude numbers, which are close to the critical value of the Froude number based on water depth.…”
Section: Introductionmentioning
confidence: 54%